2008
DOI: 10.2105/ajph.2006.097444
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health Correlates of Timing of Sexual Debut: Results From a National US Study

Abstract: Early sexual debut is associated with certain long-term negative sexual health outcomes, including increased sexual risk behaviors and problems in sexual functioning. Late initiation was also associated with sexual problems, especially among men. Further research is needed to understand how sexual initiation patterns affect later health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
273
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(302 citation statements)
references
References 34 publications
22
273
3
4
Order By: Relevance
“…7,8 Definitions of "early" FSI have varied, and include age 15 years and younger 2,4,9 or 16 years and younger, 7,10 or quartiles or tertiles of age at FSI in a study population. 11,12 Previous prospective studies have demonstrated that a range of biological, social, and psychological precursors such as early puberty, childhood adversity, low socioeconomic status, dysfunctional family relationships, absence of a biological father at home, poor school adjustment, adolescent depression, and low self-esteem are associated with earlier age at FSI. 13,14 In addition, prospective studies have revealed associations between individual child and adolescent problem behaviors largely of the externalizing type and early FSI.…”
Section: What This Study Addsmentioning
confidence: 99%
“…7,8 Definitions of "early" FSI have varied, and include age 15 years and younger 2,4,9 or 16 years and younger, 7,10 or quartiles or tertiles of age at FSI in a study population. 11,12 Previous prospective studies have demonstrated that a range of biological, social, and psychological precursors such as early puberty, childhood adversity, low socioeconomic status, dysfunctional family relationships, absence of a biological father at home, poor school adjustment, adolescent depression, and low self-esteem are associated with earlier age at FSI. 13,14 In addition, prospective studies have revealed associations between individual child and adolescent problem behaviors largely of the externalizing type and early FSI.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Religiosity has a protective association with sexual activity and number of partners (Edwards et al, 2011) but both late and early sexual debut were associated with sexual problems such as problems with arousal and orgasm among men compared to men with a normative sexual debut age (Sandfort et al, 2008).…”
Section: The Sexual Debutmentioning
confidence: 98%
“…Sandfort et al (2008) analysed data from the 1996 National Health Survey, a cross-sectional population study of adult Americans. They found that people who postponed their first sexual experience were less likely to have risky sexual partners or have sex under the influence of alcohol and drugs.…”
Section: The Sexual Debutmentioning
confidence: 99%
“…Of many factors which predispose them to high risk include the early onset of sexual activity during the teen years (Ma, 2009;Sandfort, Orr, Hirsch, & Santelli, 2008;Hallet, 2007); the probability of multiple partnerships (Shelton, 2009;Kalichman et al, 2007); general non use or inconsistent use of condoms (Cherutich, Brentlinger, Nduati, Kiarie, & Farquhar, 2008); and the reported tendency of adolescents to perceive themselves to both physically and psychologically invulnerable which in turn is related to the conduct of a variety of risk behaviors (Menser, 2010). Robbins et al, (2010) noted that in areas of high HIV seroprevalence, infection will most likely occur in adolescence with early sexual exposure and therefore suggests that programs must educate adolescents about the risk involved with specific behavior and how to reduce those risks.…”
Section: The Influence Of Hiv-aids Public Enlightenment Campaigns On mentioning
confidence: 99%